PENERAPAN PEMBELAJARAN ACTIVE LEARNING DENGAN METODE INQUIRY UNTUK MENINGKATKAN AKTIFITAS DAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPS TERPADU KOMPETENSI DASAR MENDESKRIPSIKAN HUBUNGAN ANTARA KELANGKAAN SUMBER DAYA DENGAN KEBUTUHAN MANUSIA YANG TIDAK T - Ahmad Hafas Rasyidi; ansori ansori (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2018)
Ability of professional learn of vital importance in order to improving the quality of education. Activity of repair in course of learning to teach [is] a[n form [gift/ giving] of aid which [is] program systematically and directional as according to study problem. [Gift/ giving] of the aid can in the form of a method.Used [by] Study method [is] teacher most still monoton and study of teacher centre on, one of [the] study method to increase result and aktifitas learn student and lessen depended student to teacher [is] study of inquiry which where student claimed to look for its own knowledge guided by teacher.This research aim to to know do with method of inquiry can improve result and activity learn student. Of a kind this research [is] research of [done/conducted] class action [in] MTs. Al-Hidayah Semambung, Jatibanteng - Situbondo. This Research [is] [done/conducted] by teacher acting as subject teacher of IPS Inwrought.This research [is] focussed to class of VIII semester 1 school year 2013 / 2014 amounting to 30 responder. its Method data collecting [is] method of Tes, Observation and Documentation. In this research to know result learn student hence [is] to be performed [a] [by] daily restating [at] cycle 1 and cycle 2. This daily restating [done/conducted] to measure [is] reached of study target. [done/conducted] analysis to result and activity learn student [at] this research, indicating that this research have fulfilled complete either through result and also activity learn. Student Aktifitas show livelines equal to 89% and is complete [of] classical result of learning student show 96,7%.